The Implementation Of Mamdani Fuzzy Inference In Expert System For Diagnosing Hyperthyroid Disease - Rinaldi Rinaldi; Masterjon Masterjon; Jhoanne Fredricka (Jurnal Media Computer Science, 2026)
Hyperthyroid disease is a type of cancer in which cancer cells multiply in the thyroid issue. Diagnosis of hyperthyroid disease is difficult because the symptoms of thyroid disease can vary depending on the rise and fall of thyroid hormones which inscrease the use of oxygen by body cells. However, the limited number of doctors in handling this disease make it difficult for user to consult directly about this hyperthyroid disease. So to overcome this problem, an expert system is needed to diagnose thyroid disease based on patient clinical data online to help patients or the public to consult independently. This expert system use fuzzy mamdani Method using PHP programming language and MySQL database. The result of expert system can provide convenience for useer to diagnose early hyperthyroid disease.